2012
DOI: 10.1530/joe-12-0384
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ghrelin is positively associated with body fat, liver fat and milk fat content but not with feed intake of dairy cows after parturition

Abstract: Ghrelin is a gastrointestinal peptide hormone that is present in blood mostly in a non-posttranslationally modified form, with a minor proportion acylated at Ser 3 . Both ghrelin forms were initially assigned a role in the control of food intake but there is accumulating evidence for their involvement in fat allocation and utilization. We investigated changes in the ghrelin system in dairy cows, exhibiting differences in body fat mobilization and fatty liver, from late pregnancy to early lactation. Sixteen dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
1
15
1
1
Order By: Relevance
“…Circulating total ghrelin concentrations averaged 256 ± 4 pg/mL of plasma and ranged from 108 to 508 pg/mL. Concentrations presented here are much lower than the few published reports found in dairy steers, heifers, and lactating cows, which averaged about 2,000 to 3,000 pg/mL (ThidarMyint et al, 2006;ThidarMyint and Kuwayama, 2008;Börner et al, 2013), but is more similar to baseline values reported for human total ghrelin (Cummings et al, 2004), which averaged about 300 pg/mL. It is not clear if the differences in total ghrelin concentrations between the current data and previously published data in dairy cattle are due to differences in breed or diet composition.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Circulating total ghrelin concentrations averaged 256 ± 4 pg/mL of plasma and ranged from 108 to 508 pg/mL. Concentrations presented here are much lower than the few published reports found in dairy steers, heifers, and lactating cows, which averaged about 2,000 to 3,000 pg/mL (ThidarMyint et al, 2006;ThidarMyint and Kuwayama, 2008;Börner et al, 2013), but is more similar to baseline values reported for human total ghrelin (Cummings et al, 2004), which averaged about 300 pg/mL. It is not clear if the differences in total ghrelin concentrations between the current data and previously published data in dairy cattle are due to differences in breed or diet composition.…”
Section: Discussioncontrasting
confidence: 60%
“…The biological function of des-acyl ghrelin in ruminants is unclear. The studies measuring total ghrelin in cattle have indicated a positive association with circulating NEFA, insulin, and growth hormone (ThidarMyint et al, 2006;ThidarMyint and Kuwayama, 2008;Börner et al, 2013), which could generally be attributed to the effect of ghrelin on growth hormone release. In mice, des-acyl ghrelin has been shown to decrease feed intake and gastric emptying rate, likely through effects on the hypothalamus (Asakawa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that elevated plasma NEFA concentrations around parturition are utilized for about 40% of milk fat synthesis during early lactation 12 13 . Other authors discovered that cows with greater fat mobilization produce higher milk fat contents and thus a higher ECM in early lactation 14 . In our study, ECM and milk fat content did not differ between groups in week 5 p.p.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin system is involved in eliciting feeding, inducing adiposity, and regulating glucose metabolism and body weight. Previous study revealed that plasma ghrelin is positively associated with body fat [ 26 ] which might be linked with decrease in insulin secretion [ 27 ] . Because most KPDM patients especially A−β + subgroup are obese, the role of ghrelin should be evaluated in the future study.…”
mentioning
confidence: 97%